Low-grade astrocytoma: treatment with conventionally fractionated stereotactic radiation therapy. - Kampen, Michael van; Engenhart, Rita; Debus, Jürgen; Hess, Thomas; Schad, Lothar R.; Wannenmacher, Michael (Radiology, 1996)
PURPOSE: To assess the efficacy of fractionated stereotactic radiation therapy for low-grade astrocytoma in terms of improvements to therapeutic ratio, patient survival, and quality of life. MATERIALS AND METHODS: Since 1987, 32 patients with inoperable grade II astrocytoma were irradiated. Stereotactic radiation therapy was given only to patients with progressive symptoms. The mean total dose applied was 59.8 Gy (range, 54.0-65.0 Gy). RESULTS: Four years after therapy, the overall survival rate calculated with Kaplan-Meier analysis was 76%. Median progression-free survival was 48 months. On the basis of clinical symptoms, 91% (29 of 32) of patients showed improvement or stable disease after stereotactic radiation therapy. Eleven local failures were observed, 10 of which were within the planning target volume; one patient had a continuously enlarging mass. Acute toxic effects of radiation did not exceed grade II of the World Health Organization classification. Two patients developed reversible contrast enhancement without clinical symptoms on MR images within 1 year after stereotactic radiation therapy. CONCLUSION: Stereotactic radiation therapy for grade II astrocytoma appears to improve patients' quality of life or stabilize disease and is not correlated with marginal misses.
Gesehen am 17.12.2024